Reaksi Pasar terhadap Publikasi Opini Wajar Tanpa Pengecualian dengan Paragraf Penekanan Suatu Hal - Semitayani, Ni Kadek Ayu; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 30 No 12 (2020)DO - 10.24843/EJA.2020.v30.i12.p11, 2020)
This study aims to examine the information content by looking at the market reaction to the publication of unqualified opinion with the paragraph emphasizing a matter as measured by abnormal returns and trading volume activity. This research is an event study with an observation period of 7 stock exchange days. The population in this study were manufacturing companies listed on the IDX in 2016-2018, totaling 177 companies. The sampling method used non-probability sampling with purposive sampling technique, in order to obtain a sample of 23 companies with 33 audited financial reports. The data analysis technique used paired samplesxt-test. The results of this study indicate that there is no difference in average abnormal return and average trading volume activity before and after the publication of unqualified opinion with an emphasis on a paragraph. This indicates that the publication of an unqualified opinion with an emphasis on a subject paragraph does not cause a market reaction because there is no information content on the event.  Keywords: Event Study; Abnormal Return; Trading Volume Activity .